Different management methods for tunnel abscess in tunneled cuffed catheters with catheter-related bloodstream infections and central venous stenosis: two case reports - Yafei Bai; Chunli Wang; Mingzhi Xu; Hong Li; Na An; Ruman Chen (BMC Nephrology)
Abstract Background Tunneled cuffed catheters (TCCs) are critical vascular access tools for hemodialysis patients, but they are associated with complications such as tunnel infections (TIs) and catheter-related bloodstream infections (CRBSIs). Current guidelines recommend removing infected TCCs, but this can exacerbate central venous stenosis (CVS) and complicate subsequent catheter reinsertion. This case series proposes a staged management protocol for complex TCC tunnel abscess infections complicated by CVS. Case presentation We present two cases of complex TCC tunnel abscess infections with concurrent CVS. In case 1, a 67-year-old female with ANCA-associated vasculitis had a TCC tunnel abscess and CRBSI. After TCC removal, CT angiography(CTA) revealed occlusion of the right internal jugular vein and right brachiocephalic vein, along with in-stent stenosis of the superior vena cava. Endovascular interventions, including balloon angioplasty, facilitated successful TCC reinsertion. In case 2, a 71-year-old female with diabetic nephropathy underwent a staged strategy: the infected TCC was removed and replaced with a non-cuffed catheter (NCC) in situ. After infection control, balloon angioplasty resolved CVS, and a new TCC was reinserted. Both patients achieved infection control and preserved functional vascular access. Conclusions Both patients achieved infection control and preserved functional vascular access. However, Case 1 required technically demanding multistep endovascular procedures with elevated procedural risks, while Case 2 simplified reinsertion through NCC bridging. A staged management protocol (infection control → NCC transition → endovascular salvage) effectively addresses complex TCC infections with concurrent CVS, mitigates post-removal vascular injury, and enhances reinsertion success. Larger cohort studies are warranted to validate the efficacy and long-term safety of this approach.